Densification, mechanical and thermal properties of ZrC1 − x ceramics fabricated by two-step reactive hot pressing of ZrC and ZrH2 powders. Issue 2 (February 2018) - Wei, Boxin; Chen, Lei; Wang, Yujin; Zhang, Haibin; Peng, Shuming; Ouyang, Jiahu; Wang, Dong; Zhou, Yu
Highlights: Densification behavior, mechanical and thermal properties of ZrC1 − x ceramics were studied systematacially. Dense ZrC1 − x ceramics have been fabricated by two-step reactive hot pressing at a relatively low temperature. A cubic Zr2 C-type ordered phase forms in ZC06 samples at temperature as low as 1100 o C. Abstract: Densification behavior, mechanical and thermal properties of ZrC1 − x ceramics with various C/Zr ratios of 0.6–1.0 have been investigated by two-step reactive hot pressing of ZrC and ZrH2 powders at 30 MPa and 1500–2100 °C. The two-step reactive hot pressed ZrC1 − x ceramic has a higher relative density (> 95.3%) than that (91.9%) of stoichiometric ZrC sintered at 2100 °C. A cubic Zr2 C-type ordered phase forms in the ZrC1 − x sample obtained at a ZrC/ZrH2 molar ratio of 0.6 at a relatively low temperature of 1100 °C. The decrease in C/Zr ratio is beneficial to densification of ZrC1 − x ceramic, however, excess grain growth occurs after sintering above densification temperature. The elastic modulus and Vickers hardness decrease with decreasing the C/Zr ratio. With decreasing the C/Zr ratio, both thermal conductivity and specific heat decrease due to the enhanced scattering of conducting phonons and electrons by carbon vacancies.